2017
DOI: 10.1108/jica-12-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Early findings from the evaluation of the Integrated Care and Support Pioneers in England

Abstract: PurposeIntegrating health and social care is a priority in England, although there is little evidence that previous initiatives have reduced hospital admissions or costs. Twenty-five Integrated Care Pioneers have been established to drive change 'at scale and pace'. The early phases of our evaluation (April 2014-June 2016) aimed to identify their objectives, plans and activities, and to assess the extent to which they have overcome barriers to integration. In the longer-term, we will assess whether integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 5 publications
1
97
0
Order By: Relevance
“…Little is known about how ACOs engage patients and their families in shared decision making and improving care, but there is some evidence that patients receiving care from more patient centred practices report better outcomes 49. In England, STPs have struggled to involve clinicians, patients, and local authorities28—just like the integrated care pioneers that preceded them 50. The extent to which this engagement can be strengthened is likely to be a major determinant of success for new care models in future.…”
Section: Lessons For the English Nhsmentioning
confidence: 99%
“…Little is known about how ACOs engage patients and their families in shared decision making and improving care, but there is some evidence that patients receiving care from more patient centred practices report better outcomes 49. In England, STPs have struggled to involve clinicians, patients, and local authorities28—just like the integrated care pioneers that preceded them 50. The extent to which this engagement can be strengthened is likely to be a major determinant of success for new care models in future.…”
Section: Lessons For the English Nhsmentioning
confidence: 99%
“…Significantly, the inclusion of patients, their carers and service users within WSIC programmes has been a prominent feature associated with their success (Erens et al, 2015). This initiative as part of the integration of services involved lay partners both challenging and raising concerns with those leading the redesign but in turn it appeared that they also act as advocates for the change, championing it within their communities.…”
Section: Patient and Service User Involvementmentioning
confidence: 99%
“…Initial evaluation of these have suggested that their success has been attributed to sound, effective management, leadership and governance structures. However, it has been noted that within these programmes, when there was a change of leadership or an alteration in the management arrangements the integration process was somewhat weakened and the credibility of the process reduced with those clinical staff involved (Erens et al, 2015). Coupe (2013) also suggested that as it takes between 3-5 years for integrated team working to reach its full potential, sustained leadership and management support is essential.…”
Section: Leadership and Managementmentioning
confidence: 99%
“…Of concern then are recent findings that pressures on local budgets have led commissioners to retrench from a focus on long-term planning and prevention to fire-fight more immediate pressures. 31 A key challenge for local agencies is identifying people who are potentially vulnerable during cold weather but who are not known to services. One approach adopted by some localities is to remind any staff who come into contact with the public, for whatever reason, to 'keep an eye out' and to signpost or refer people they are concerned about.…”
Section: Discussionmentioning
confidence: 99%